Pengaruh Work Life Balance, Program Pelatihan dan Lingkungan Kerja Terhadap Kinerja Karyawan di PT Juanindo Perkasa - Salsabila, Adinda; Muttaqin, Ridlwan; Herlina, Listri (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2025)
This study aims to examine the effect of Work Life Balance, Training Programs, Work Environment on Employee Performance at PT Juanindo Perkasa. The research method used is a quantitative approach. The study population consisted of 124 employees of PT Juanindo Perkasa. The research sample was determined using the Slovin formula with a significance level of 0.10 totaling 56 people. The data collection technique used was questionnaire observation. The collected data were then analyzed using statistical techniques including descriptive analysis, verification analysis, determination coefficient analysis and partial and simultaneous hypothesis testing using the SPSS 26 program. The results of the study showed that Work Life Balance had a significant effect on employee performance, Training Programs had a significant effect on employee performance, Work Environment had a significant effect on employee performance, and Work Life Balance, Training Programs, Work Environment together had a positive and significant effect on employee performance.